Moore's Paradox and Self-Knowledge - WILLIAMS, John N. (Institutional Knowledge at Singapore Management University, 2004)
What explanation is there of the source of my justification for my beliefs about my beliefs that respects the fact that I am normally the best authority on them? Moore's paradox demands an explanation of the absurdity of believing or asserting possible truths of the forms p but I don't believe that p or p but I believe that not-p. I argue for Evans principle that whatever justifies me in believing that p also justifies me in believing that I believe that p. This helps explain how I come to know my own beliefs and also shows that it is impossible for a Moorean belief to be justified. I then explain the absurdity of Moorean assertion while avoiding the messy notion of 'expressing belief' yet acknowledging Shoemaker’s constraint that if I cannot non-absurdly believe that p then I cannot non-absurdly assert that p.